Dissection of the genetic architecture for grain quality‐related traits in three RIL populations of maize (Zea mays L.). Issue 1 (5th November 2015) - Wang, Zhiyong; Liu, Na; Ku, Lixia; Tian, Zhiqiang; Shi, Yong; Guo, Shulei; Su, Huihui; Zhang, Liangkun; Ren, Zhenzhen; Li, Guohui; Wang, Xiaobo; Zhu, Yuguang; et al.
Abstract: To manipulate the composition of the maize kernel to meet future needs, an understanding of the molecular regulation of kernel quality‐related traits is required. In this study, the quantitative trait loci (QTL) for the concentrations of grain protein, starch and oil were identified using three sets of RIL populations in three environments. The genetic maps and the initial QTL were integrated using meta‐analyses. A total of 38 QTL were identified, including 15 in population 1, 12 in population 2 and 11 in population 3. The individual effects ranged from 2.87% to 13.11% of the phenotypic variation, with seven QTL each contributing over 10%. One common QTL was found for the concentrations of grain protein and starch in bin 3.09 in the three environments and the three RIL populations. Of the 38 initial QTL, 22 were integrated into eight mQTL by meta‐analysis. mQTL3 and mQTL8 of the key mQTL in which the initial QTL displayed R 2  > 10% included six and three initial QTL for grain protein and starch concentrations from two or three populations, respectively. These results will provide useful information for marker‐assisted selection to improve the quality of the maize kernel.